2006
DOI: 10.1073/pnas.0604104103
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase δ regulates protein kinase C and epidermal growth factor receptor signaling

Abstract: Diacylglycerol kinases (DGKs) phosphorylate diacylglycerol (DAG) to terminate its signaling. To study DGK␦, we disrupted its gene in mice and found that DGK␦ deficiency reduced EGF receptor (EGFR) protein expression and activity. Similar to EGFR knockout mice, DGK␦-deficient pups were born with open eyelids and died shortly after birth. PKCs are activated by DAG and phosphorylate EGFR to reduce its expression and activity. We found DAG accumulation, increased threonine phosphorylation of EGFR, enhanced phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 41 publications
3
85
0
Order By: Relevance
“…Several reports have shown that activated JNK positively regulates EGFR expression via c-Jun activation (27)(28)(29), and we investigated whether COX-2 regulates JNK activity, resulting in EGFR down-regulation in the tested cancer cells. Overexpressed COX-2 specifically activated JNK compared with control cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that activated JNK positively regulates EGFR expression via c-Jun activation (27)(28)(29), and we investigated whether COX-2 regulates JNK activity, resulting in EGFR down-regulation in the tested cancer cells. Overexpressed COX-2 specifically activated JNK compared with control cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that c-Jun transcription factor, a substrate of JNK, positively regulates transcription of the EGFR gene (27)(28)(29). Therefore, we investigated whether JNK is involved in COX-2-induced EGFR down-regulation.…”
Section: Cox-2-activated Jnk Negatively Regulates Egfr Expressionmentioning
confidence: 99%
“…DGKδ -KO mice have eyelids open at birth and die soon because of the respiratory diffi culty (Crotty et al 2006). The study on isolated cells reveals that DGKδ -defi ciency reduces EGF receptor (EGFR) protein expression and activity.…”
Section: Animal Models and Knockout Micementioning
confidence: 99%
“…Functional analyses of DGK isozymes have been performed on knockout mice of DGKs, including DGKα (Olenchock et al 2006), DGKζ (Zhong et al 2003), DGKδ (Crotty et al 2006), DGKε (Rodriguez de Turco et al 2001), and DGKι (Regier et al 2005). DGKα and DGKζ are implicated in T cell receptor (TCR) signaling, especially T cell anergy.…”
Section: Animal Models and Knockout Micementioning
confidence: 99%
“…Perhaps most intriguing of these is DGKQ, due to its identification in genome-wide association studies as a PD risk factor. The lipid kinase family of DGKs catalyzes the conversion of diacylglycerol to phosphatidic acid and thereby regulate events downstream of these two lipid signals in part by antagonizing PKC activation by diacylglycerol (44,45). DGKQ activity in turn is inhibited by GTP-bound RhoA (46).…”
Section: Volume 287 • Number 40 • September 28 2012mentioning
confidence: 99%